Uczeń i Mistrz. O relacji Ryszarda Ordyńskiego i Maxa Reinhardta (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The work of Max Reinhardt (1873–1943) is described in Polish theater studies in many aspects. This multitalented director inspired many theater makers, but few Polish directors had such a close professional relationship with him as Ryszard Ordyński (1878–1953). Focusing on reconstructing the student-master relation-ship, I discuss the nature of Ordyński's collaboration with the Deutsches Theater team, as well as his subsequent migrations across Europe and the United States, dur-ing which he collaborated with many theater reformers of the early 20th century.